Kebijakan Pendidikan di Indonesia: Evaluasi terhadap Rumusan Kebijakan Kurikulum Bidang Pendidikan Tinggi - Binsar Antoni Hutabarat (Societas Dei: Jurnal Agama dan Masyarakat, 2017)
ABSTRACT: This article entitled, The Policy of Education in Indonesia: An Evaluation towards The Formula of Curriculum Policy for Higher Education focuses on the study of the formulation of curriculum policy which refers to the framework of national qualification in Indonesia. This research uses qualitative method: the data was gathered through an interview, questionnaire distribution, and observation on three tertiary institutions in Indonesia, also secondary data in the form of selected books. This research finds that a curriculum policy which refers to the framework of national qualification in Indonesia is an elite product and weak in terms of socialization, and the consequence of this policys application is not as expected. policy.Â KEYWORDS: policy of education, evaluation of policy, higher education, higher education curriculum